Նորի և ավանդականի համադրությունը Համո Սահյանի պոեզիայում - Սառաջյան, Զարինե («Դիզակ պլյուս» հրատարակչություն)
Новое обычно основывается на традиционном. В армянской литературе отношение традиционного и нового всегда было актуальным. В этом плане выделяется лирика Амо Сагяна. Писатель творчески усвоил богатые традиции армянской и зарубежной литературы, его мысли питаются неиссякаемым источником национального и народного мышления, родной земли, неповторимой природы, богатого опыта наших классиков. Писатель сочетает, синтезирует старое и новое. The new is usually based on the traditional. In the Armenian literature the relation between the traditional and the new was always actual. In this regard the lyric poetry of Hamo Sahyan is distinguished. The poet acquired creatively the rich traditions of the Armenian and foreign literature, his thoughts are enriched with inexhaustible source of the national thinking, native land, unique nature, rich experience of our classics. The writer combines, synthesizes the new and the traditional.
Keywords: Գրականություն